Success Factors for the Establishment of a Pan-African Securities Exchange - Foster, Andrew (My University, 2011)
This research investigated the critical success factors for the establishment of a pan-African securities exchange. Interviews with participants from the financial markets from around Africa enabled 16 critical success factors to be identified. These were then categorised into three sub-categories: catalysts for growth, challenges, and absolute requirements for the establishment of such an exchange. Catalysts for growth are factors from which the growth of an exchange would benefit if these factors were in place. Challenges are factors that individually represent varying levels of dependence for the successful establishment of such an exchange but collectively form a key requirement for the successful establishment of a pan-African securities exchange. Absolute requirements represent those requirements without which the establishment of a pan-African exchange would not be successful. The key findings are that despite the numerous and often difficult critical success factors required, it would not be an impossible task to create a regional exchange or even a pan-African exchange
MBA - WBS
Keywords: Pan-African Securities Exchange; Stock exchanges; Financial markets